Categorising e-learning - Amy Dunn Wilson (Flexible Learning Association of New Zealand, 2012)
Categorising-learning is almost as problematic as defining the term. In an attempt to quantify/qualify the level of e-learning use in the tertiary sector in New Zealand, the Ministry of Education (MoE) established a classification system for courses in the tertiary sector. The value of this tool has been disputed and a new system was proposed, but later withdrawn. The MoE has now asked for further discussion on the issue and has also considering abandoning the classification system. The purpose of this study is two-fold, first to consider the Ministry's system to gain a better understanding of how e-learning is classified and second to recommend changes to this system that might be more practical in terms of institutional and sector analysis and planning. The study uses definitions from literature to compare and contrast the models. The study found that the e-learning managers did express concern over the ambiguity within the levels of the current classification system and additionally over who is responsible for the recording of e-learning use in their institutions. The study proposed additional classification systems that may provide greater clarity to those responsible for classifying courses. In addition it found that other institutional processes may need to be considered to solve the issues of who has responsibility over and access to the classification of e-learning use.